The Influencing Of Understanding Profit Sharing And Understanding Margin On Islamic Financial Behaviour - Rahmayati, Rahmayati; Mujiatun, Siti; Hayati, Isra; Badawi, Afif (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research aims to determine and analyze the influence of understanding profit sharing and margins on Sharia financial behavior according to the understanding of the public and employees of Bank Syariah Indonesia, Pematang Siantar City. The implication is customers who possess greater financial literacy about these concepts may make better decisions and select investment products that better suit their moral convictions and financial objectives. This thesis's research type is quantitative, and the data used is primary. The population used in this research was the local community and BSI Pematang Siantar City employees, totaling 150 people, and the sampling technique used the Slovin formula with n=109. Data analysis techniques using descriptive tests, data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The data processing uses the SPSS version 22.0 program. The research results show that: (1) The model estimation shows that the R Square value is 0.775. This means that 77.5% of the independent variables in this model influence the dependent variable. Other variables outside this model influence the remaining 22.5%; (2) The regression model shows that understanding profit sharing significantly affects Sharia financial behavior, and understanding margin significantly affects Sharia financial behavior.